Factors Influencing Customer Satisfaction In Purchasing Consumer Goods - Cindy Octavia; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
This study aims to investigate what factors can affect customer satisfaction in buying consumer goods. The population in this study were all users of Pepsodent toothpaste. Data were taken from 270 respondents using PLS SEM which helps in analyzing data and testing research hypotheses. The results of this study are perceived quality has a positive effect on customer satisfaction, perceived value of cost has a positive effect on customer satisfaction, brand identification has a positive effect on customer satisfaction, brand trust has a positive effect on customer satisfaction, lifestyle congruence has a positive effect on customer satisfaction, and brand identification has a positive effect. on customer satisfaction, brand awareness has a positive effect on customer satisfaction, customer satisfaction has a positive effect on brand loyalty, customer satisfaction mediates the influence of consumer-based brand equity dimensions, namely perceived quality, perceived value of cost, brand identification, brand trust, lifestyle congruence, brand identification , brand awareness, to brand loyalty.